Preparation and Enhanced Oil Recovery Mechanisms of Janus-SiO2-Reinforced Polymer Gel Microspheres - Fei Gao; Baolei Liu; Yuelong Liu; Lei Xing; Yan Zhang (Gels, 2025)
In order to improve oil recovery efficiency in low-permeability reservoirs, this study developed amphiphilic Janus-SiO2 nanoparticles to prepare polymer gel microspheres for enhanced oil recovery (EOR). Firstly, Janus-SiO2 nanoparticles were synthesized via surface modification using (3-aminopropyl)triethoxysilane and α-bromoisobutyryl bromide. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) characterization confirmed the successful grafting of amino and styrene chains, with the particle size increasing from 23.8 nm to 32.9 nm while maintaining good dispersion stability. The Janus nanoparticles exhibited high interfacial activity, reducing the oil–water interfacial tension to 0.095 mN/m and converting the rock surface wettability from oil-wet (15.4°) to strongly water-wet (120.6°), thereby significantly enhancing the oil stripping efficiency. Then, polymer gel microspheres were prepared by reversed-phase emulsion polymerization using Janus-SiO2 nanoparticles as emulsifiers. When the concentration range of nanoparticles was 0.1–0.5 wt%, the particle size range of polymer gel microspheres was 316.4–562.7 nm. Polymer gel microspheres prepared with a high concentration of Janus-SiO2 nanoparticles can ensure the moderate swelling capacity of the particles under high-temperature and high-salinity conditions. At the same time, it can also improve the mechanical strength and shear resistance of the microspheres. Core displacement experiments confirmed the dual synergistic effect of this system. Polymer gel microspheres can effectively plug high-permeability zones and improve sweep volume, while Janus-SiO2 nanoparticles enhance oil displacement efficiency. Ultimately, this system achieved an incremental oil recovery of 19.72%, exceeding that of conventional polymer microsphere systems by more than 5.96%. The proposed method provides a promising strategy for improving oil recovery in low-permeability heterogeneous reservoir development.